1996
DOI: 10.2527/1996.7461288x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of wide calcium:phosphorus ratios on supplemental phytase efficacy for weanling pigs fed two dietary phosphorus levels.

Abstract: Ninety-six weanling pigs (initial BW = 9.3 kg, initial age = 37 d) were used in a 4-wk experiment to evaluate the response to three Ca: total (t) P ratios (1.2:1, 1.6:1, or 2.0:1) fed in combination with two P levels (.07 or .16% available that correspond to .36 or .45% tP) and two phytase levels (PY; 700 or 1,050 units/kg of diet). A 3 x 2 x 2 factorial arrangement of treatments was employed using a corn-soybean meal diet. Performance, serum mineral concentrations and alkaline phosphatase (ALP) activity, Ca a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
80
6
5

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(105 citation statements)
references
References 15 publications
14
80
6
5
Order By: Relevance
“…Assessing the effects of high Ca:P (1.2:1, 1.6:1, and 2.0:1), with two levels of dietary phosphorus (0.360 and 0.435%), and phytase supplementation in piglets, Qian et al (1996) found that the ADG and feed efficiency decreased linearly as Ca:P ratio increased in the diets. The authors associated the lower performance to a possible negative effect of calcium excess on phosphorus absorption in the small intestine of pigs as a result of insoluble complexes formation, especially when the dietary phosphorus is below the required by the pigs.…”
Section: Resultsmentioning
confidence: 99%
“…Assessing the effects of high Ca:P (1.2:1, 1.6:1, and 2.0:1), with two levels of dietary phosphorus (0.360 and 0.435%), and phytase supplementation in piglets, Qian et al (1996) found that the ADG and feed efficiency decreased linearly as Ca:P ratio increased in the diets. The authors associated the lower performance to a possible negative effect of calcium excess on phosphorus absorption in the small intestine of pigs as a result of insoluble complexes formation, especially when the dietary phosphorus is below the required by the pigs.…”
Section: Resultsmentioning
confidence: 99%
“…The NRC (1988) reports that the optimal Ca:P ratio in pig diets is between 1:1 and 1.5:1 for grain-soyabean meal based diets. However, when phytase was added to pig diets Qian et al (1996) found that P digestibility was decreased when the Ca:tP ratio was increased from 1.2:1 to 1.6:1. Ideally, the Ca:P ratio should be based on available Ca and P instead on total Ca and P. However, many more studies are needed to generate a reliable data base for available Ca and P values from various grain sources.…”
Section: Discussionmentioning
confidence: 99%
“…The range of equivalency values for 500 U/kg phytase is larger ranging from 0.64 g P to 2.47 g P. Factors which may influence these equivalency value estimates include: the basal level of P, the age of the animal, the response criteria used, and perhaps most importantly the ratio of Ca to P. Qian et al (1996) reported a detrimental effect of a widening Ca:tP ratio in excess of 1.2:1 on phytase efficacy in pigs. In the pig studies of Jongbloed et al (1996a), Kornegay and Qian (1996) , and Yi et al (1996) only two levels of P were fed, so the response of various criteria to P was assumed to be linear.…”
Section: Discussionmentioning
confidence: 99%
“…BW 5 body weight; Ca 5 calcium; P 5 phosphorus; tP 5 total P; PP 5 phytate P; NPP 5 non-phytate P; NPPp 5 non-phytate P from plant sources; NPPm-a 5 non-phytate P from mineral and animal sources; PhytP 5 plant phytase; PhytM 5 microbial phytase; ADG 5 average daily gain; ADFI 5 average daily feed intake. (1992, 1996 and 2000), Kemme et al (1997a, 1997b, 1999a and 1999b) (1984( , 1985( , 1987a( and 1987b( ), Qian et al (1996, Values and numbers from experimental groups related to diets containing plant and microbial phytase only; FTU, phytase unit.…”
Section: Data Collection and Codingmentioning
confidence: 99%